2013
DOI: 10.1111/jasp.12080
|View full text |Cite
|
Sign up to set email alerts
|

Using peer injunctive norms to predict early adolescent cigarette smoking intentions

Abstract: The present study investigated the importance of the perceived injunctive norm to predict early adolescent cigarette smoking intentions. A total of 271 6th graders completed a survey that included perceived prevalence of friend smoking (descriptive norm), perceptions of friends’ disapproval of smoking (injunctive norm), and future smoking intentions. Participants also listed their five best friends, in which the actual injunctive norm was calculated. Results showed that smoking intentions were significantly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 46 publications
(58 reference statements)
1
27
0
Order By: Relevance
“…A focus theory of normative conduct posits that individuals are more likely to engage in a behavior when they believe that important others think they should participate in that behavior (i.e., injunctive norms) and when individuals perceive that others around them are partaking in that behavior (i.e., descriptive norms). Previous studies have shown that injunctive norms (Zaleski & Aloise‐Young, ) and descriptive norms (Brooks‐Russell, Simons‐Morton, Haynie, Farhat, & Wang, ) are significantly associated with adolescents' drinking and smoking intentions and actual behaviors. In addition to injunctive and descriptive norms, Elek, Miller‐Day, and Hecht () added personal norms (i.e., internalized moral values of right and wrong) by examining adolescents' own beliefs regarding whether they should use substances.…”
Section: Primary Socialization Theory and Peer Influences On Substancmentioning
confidence: 99%
“…A focus theory of normative conduct posits that individuals are more likely to engage in a behavior when they believe that important others think they should participate in that behavior (i.e., injunctive norms) and when individuals perceive that others around them are partaking in that behavior (i.e., descriptive norms). Previous studies have shown that injunctive norms (Zaleski & Aloise‐Young, ) and descriptive norms (Brooks‐Russell, Simons‐Morton, Haynie, Farhat, & Wang, ) are significantly associated with adolescents' drinking and smoking intentions and actual behaviors. In addition to injunctive and descriptive norms, Elek, Miller‐Day, and Hecht () added personal norms (i.e., internalized moral values of right and wrong) by examining adolescents' own beliefs regarding whether they should use substances.…”
Section: Primary Socialization Theory and Peer Influences On Substancmentioning
confidence: 99%
“…Research provides evidence that supports the influence of peers’ (dis)approval and parents’ (dis)approval on adolescents’ smoking and intention [2023, 36, 37], but while peer influence increases with adolescents’ age, parent influence decreases [21, 36]. …”
Section: Introductionmentioning
confidence: 99%
“…10 Peer norms or perception of peer smoking has also been shown to influence smoking prevalence. 11,12 The overwhelming majority of Not mutually exclusive categories, participants could select more than one category. respondents, regardless of their smoking status, overestimated the smoking prevalence on campus.…”
Section: Discussionmentioning
confidence: 99%